2017
DOI: 10.1371/journal.pone.0179436
|View full text |Cite
|
Sign up to set email alerts
|

DOT1L inhibitor improves early development of porcine somatic cell nuclear transfer embryos

Abstract: Incomplete epigenetic reprogramming of the genome of donor cells causes poor early and full-term developmental efficiency of somatic cell nuclear transfer (SCNT) embryos. Previous research indicate that inhibition of the histone H3 K79 methyltransferase DOT1L, using a selective pharmacological inhibitor EPZ004777 (EPZ), significantly improved reprogramming efficiency during the generation of mouse induced pluripotent stem cells. However, the roles of DOT1L in porcine nuclear transfer-mediated cellular reprogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…anti-H3K4me2 rabbit polyclonal 1/500 Millipore (07-030) [13][14][15] anti-H3K4me3 rabbit polyclonal 1/500 Abcam (ab8580) [16][17][18] anti-H3K9me3 rabbit polyclonal 1/500 Abcam (ab8898) [19][20][21] anti-H3K27ac rabbit polyclonal 1/500 Abcam (ab4729) [22][23][24] anti-H3K27me2 rabbit polyclonal 1/500 Abcam (ab24684) [25,26] anti-H3K27me3 rabbit polyclonal 1/500 Millipore (07-449) [24,[27][28][29] anti-H3K79me2 rabbit polyclonal 1/500 Abcam (ab3594) [30][31][32] anti-H3K79me3 rabbit polyclonal 1/500 Abcam (ab2621) [33][34][35] anti-SCP3 mouse monoclonal 1/500 Abcam (ab97672) [36][37][38] anti-α-Tubulin (S2 Fig) mouse monoclonal 1/500 Sigma-Aldrich (T6199) [39,40] All antibodies are commercially available, and their specificity has been reported in previous studies.…”
Section: Antibody Name Source Dilution Company (Catalogue) Referencementioning
confidence: 99%
“…anti-H3K4me2 rabbit polyclonal 1/500 Millipore (07-030) [13][14][15] anti-H3K4me3 rabbit polyclonal 1/500 Abcam (ab8580) [16][17][18] anti-H3K9me3 rabbit polyclonal 1/500 Abcam (ab8898) [19][20][21] anti-H3K27ac rabbit polyclonal 1/500 Abcam (ab4729) [22][23][24] anti-H3K27me2 rabbit polyclonal 1/500 Abcam (ab24684) [25,26] anti-H3K27me3 rabbit polyclonal 1/500 Millipore (07-449) [24,[27][28][29] anti-H3K79me2 rabbit polyclonal 1/500 Abcam (ab3594) [30][31][32] anti-H3K79me3 rabbit polyclonal 1/500 Abcam (ab2621) [33][34][35] anti-SCP3 mouse monoclonal 1/500 Abcam (ab97672) [36][37][38] anti-α-Tubulin (S2 Fig) mouse monoclonal 1/500 Sigma-Aldrich (T6199) [39,40] All antibodies are commercially available, and their specificity has been reported in previous studies.…”
Section: Antibody Name Source Dilution Company (Catalogue) Referencementioning
confidence: 99%
“…Taking bovine as an example, large offspring syndrome (LOS) is the most common abnormal development, resulting in a severe loss of the cloned offspring in perinatal period (Smith, Suzuki et al 2012). Numerous studies have reported that the incomplete epigenetic reprogramming of nuclear donor cells is a main cause for low embryonic development efficiency and abnormality of cloned offspring (Akagi, Geshi et al 2013, Tao, Zhang et al 2017. The common epigenetic reprogramming occurring during early embryonic development includes DNA methylation, histone modification, and chromatin remodeling (Betthauser, Pfister-Genskow et al 2006).…”
Section: Scnt Has Become a Powerful Technique And Shown Great Promisementioning
confidence: 99%
“…In addition, MM‐102 increased blastocyst formation rates and total cell numbers, contributing to the production of cloned porcine embryos (Zhang et al, ). Tao et al () observed that the selective inhibitor EPZ00477 (EPZ) of a histone H3K79 methyltransferase, DOT1L, restored H3K79me2 levels to those observed in IVF embryos, increased the blastocyst rate of porcine SCNT embryos, and elevated expression of genes associate with pluripotency. Similarly, co‐treatment with TSA and BIX‐01294, an inhibitor of G9a histone methyltransferase that reduces H3K9me2 levels in somatic cells, corrected abnormal H3K9me2 and 5mC (DNA methylation) levels in 4‐cell stage and trophectoderm lineage of SCNT blastocysts and increased the expression of genes related to lineage differentiation when compared to in vivo‐ and in vitro‐fertilized embryos (Cao et al, ).…”
Section: Transcriptomic and Metabolomic Approaches To Understand Preimentioning
confidence: 99%
“…In addition, MM-102 increased blastocyst formation rates and total cell numbers, contributing to the production of cloned porcine embryos (Zhang et al, 2018). Tao et al (2017) observed that the selective inhibitor EPZ00477 (EPZ) of a histone H3K79 methyltransferase, DOT1L, restored H3K79me2 levels to those observed in IVF embryos, increased the blastocyst rate of porcine SCNT embryos, and elevated expression of genes associate with pluripotency.…”
Section: Strategies For Epigenetic Regulation Of Scnt-derived Embryosmentioning
confidence: 99%